2020
DOI: 10.1016/j.msard.2020.102449
|View full text |Cite
|
Sign up to set email alerts
|

Would it be recommended treating multiple sclerosis relapses with high dose oral instead intravenous steroids during the COVID-19 pandemic? Yes

Abstract: The emergence of novel Coronavirus 2019 and the subsequent pandemic are presenting a challenge to neurologists managing patients with multiple sclerosis (MS). The clinical management has dramatically altered and it was necessary to change and/or adapt it to the new situation. Regarding relapses management, the use of intravenous corticosteroids and hospitalization during MS relapses increase the risk of viral exposure. Objective: To review the efficacy and safety of high dose oral corticosteroids in acute rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, systemic infections are associated with an increased risk of MS relapse. 12 COVID-19 infection was not related to the worsening of MS in most patients. Deterioration of the clinical condition in MS patients may be observed during infection or fever.…”
Section: Discussionmentioning
confidence: 77%
“…However, systemic infections are associated with an increased risk of MS relapse. 12 COVID-19 infection was not related to the worsening of MS in most patients. Deterioration of the clinical condition in MS patients may be observed during infection or fever.…”
Section: Discussionmentioning
confidence: 77%
“…In the current epidemiological scenario, neurologists may consider the new evidence on the similar efficacy of both oral and IV steroids for attacks. 44 Using oral steroids during the pandemic would be an useful and safe option for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness and the safety of high-dose corticosteroids orally administered to treat MS relapses has been well documented in many studies ( Alam et al, 1993 ; Le Page et al, 2015 ; Martinelli et al, 2009 ; Morrow et al, 2018 ; Ramo-Tello et al, 2014 ). In recent reviews and meta-analyses, authors identified clinical trials providing evidence that high doses of oMP have similar efficacy as ivMP in reducing EDSS score and gadolinium enhancing lesions in the MRI scan of MS patients ( Lattanzi et al, 2017 ; Liu et al, 2017 ; Martinelli et al, 2009 ; Segamarchi et al, 2020 ). In our study, we included MS patients and also one NMOSD patient with a severe relapse.…”
Section: Discussionmentioning
confidence: 99%
“…They may be preferable to ivCS for some patients with an MS relapse (Burton et al, 2012) and could represent a remarkable option in order to spare our patients the risk of SARS-CoV-2 transmission (Brownlee et al, 2020;Segamarchi et al, 2020). Unfortunately, oral methylprednisolone (oMP) is not available in Argentina like in other countries.…”
Section: Introductionmentioning
confidence: 99%